Cognitive Dysfunction and Neuroinflammation After an aSAH - Mosley, Mary (MD Conference Express, 2015)
Cognitive dysfunction occurs after an aneurysmal subarachnoid hemorrhage, affecting psychosocial behavior, activities of daily living, and return to work. The mechanisms for the cognitive deficits are not understood, but neuroinflammation appears to be one process. New therapies to target neuroinflammation are being studied.